GROWTH CURVE ANALYSIS OF BACTERIAL ISOLATES FROM FRESH COAL MINE SPOIL - BEHERA, NIRANJAN; SETHY, KHULANA (The Bioscan, 2010)
The study deals with growth curve analysis of a Gram negative bacilli and a Gram negative cocci, isolated from fresh coal mine spoil, over a temperature range of 35-50ºC. The analysis indicated normal optimal growth curve for both the isolates at 35ºC. However with increase in temperature, both the isolates showed deviated growth curve with reduction in the exponential phase and specific growth rate. The study concludes both the isolates to be mesophilic with capacity to tolerate higher temperature regime.